Implementation of Practicum Worksheets Based on Guided Inquiry on the Topic of Colloids to Improve Students' Science Process Skills - Triannisa Rahmawati*; Hokcu Suhanda; Friska Istighfari Aulia Sabilla; Asep Suryatna (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
Currently, a lot of learning focuses on cognitive achievement, which results in less involvement of students in learning. Whereas in the renewable curriculum students are required to have ability incognitive, affective and psychomotor. One of these psychomotor aspects is science process skills by applying inquiry model. This study aims to determine the effect of the implementation of guided inquiry-based practicum worksheets on colloid topics on students' science process skills. The research method used mixed research method research with concurrent triangulation designs. The research was conducted in Cimahi, involving 33 students of class XII and 5 validators consisting of two lecturers and three teachers. The research instruments were used self-assessment, observation sheets for practicum activities using guided inquiry-based worksheets, assessment of student worksheet’s assignments, and restricted-response essays. The enhancement of science process skills was calculated by the N-gain formula using pretest and posttest score and characterize into high, medium and low. The results showed that the improvement of student science process skills on the topic of emulsifiers was in the medium category with an N-gain value of 0.6. The implementation of the practicum using guided inquiry-based worksheets on the result of self-assessment obtained 82.0%, the results of observation obtained 82.9%, and the assessment of student’s assignment in the worksheets obtained 81.6% in which all in the very good category